If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 3x^{2}+ -5x + -28 = 2x^{2}+ x + -28 Reorder the terms: -28 + -5x + 3x^{2}= 2x^{2}+ x + -28 Reorder the terms: -28 + -5x + 3x^{2}= -28 + x + 2x^{2}Add '28' to each side of the equation. -28 + -5x + 28 + 3x^{2}= -28 + x + 28 + 2x^{2}Reorder the terms: -28 + 28 + -5x + 3x^{2}= -28 + x + 28 + 2x^{2}Combine like terms: -28 + 28 = 0 0 + -5x + 3x^{2}= -28 + x + 28 + 2x^{2}-5x + 3x^{2}= -28 + x + 28 + 2x^{2}Reorder the terms: -5x + 3x^{2}= -28 + 28 + x + 2x^{2}Combine like terms: -28 + 28 = 0 -5x + 3x^{2}= 0 + x + 2x^{2}-5x + 3x^{2}= x + 2x^{2}Solving -5x + 3x^{2}= x + 2x^{2}Solving for variable 'x'. Reorder the terms: -5x + -1x + 3x^{2}+ -2x^{2}= x + 2x^{2}+ -1x + -2x^{2}Combine like terms: -5x + -1x = -6x -6x + 3x^{2}+ -2x^{2}= x + 2x^{2}+ -1x + -2x^{2}Combine like terms: 3x^{2}+ -2x^{2}= 1x^{2}-6x + 1x^{2}= x + 2x^{2}+ -1x + -2x^{2}Reorder the terms: -6x + 1x^{2}= x + -1x + 2x^{2}+ -2x^{2}Combine like terms: x + -1x = 0 -6x + 1x^{2}= 0 + 2x^{2}+ -2x^{2}-6x + 1x^{2}= 2x^{2}+ -2x^{2}Combine like terms: 2x^{2}+ -2x^{2}= 0 -6x + 1x^{2}= 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-6 + x) = 0## Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0## Subproblem 2

Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Simplifying x = 6## Solution

x = {0, 6}

| 0.6(x+70)+0.2x=58 | | 3x+x+6=-18 | | 6x^2+23x=35 | | 7=47(x+7) | | 490+x=x*3 | | 10x+9=6x+9 | | 34x^2-4x+8=100 | | 6(x+3)=9+6x | | 2x=4x-4 | | x^2(x^2-64)-4(x^2-64)=0 | | 5t-5/9=22/9 | | 5t-5/9=22-9 | | 9x-21+2x+18=96 | | 23-10x=2 | | a-6=-9 | | 4x-48=7(x-6) | | 2xy*2y=600 | | 7x-2=3x-9 | | 9x^2-73x+114=0 | | 0.70x+0.50(100-x)=60 | | 8x-64+4x-40=44 | | 3y=11-x | | F=2000(1+2) | | 4x+4=7x+3 | | -4x+2=-1 | | w^2-6w=0 | | x+x+33+4x-31=710 | | 15+x=-10 | | 2p^2-11p+5=0 | | m+1=2 | | 4x+1-2x+1=8x+3-x+1 | | 45+67= | | x-7x-12=-20 | | A=pirh | | -3v+11=-8v+51 | | -9w+8w+3=-4 | | 2-3x=22+2x | | 4+5=27 | | 120=2x-15+7x | | 5X=0.8(-2+5X) | | 1b-9+86=30 | | m/3+m/7= | | 0.8(-2+5X)=5X | | 56.25=9x^2 | | 0.8(-2+5)=5X | | 2(4t-2)=16-2t | | -7(3w-4)=7(3w+7) | | 3x^2+x^2+12x+20=180 | | 18x-98=15x+46 | | b(5px-3c)=a(qx-4) | | 6*5-4f=26 | | 1.5(14X+2)=3(2-3X) | | t(9t+1)=8 | | 6(5-4f)=26 | | 4x+40+32y=0 | | 2*8+22c=32 | | 3x+23/5+x+10/7=9 | | 2(5z-3)-4(z-2)= | | 12x-4y+16=0 | | .18y+.02(y+9000)=780 | | -.10(58)+.65x=.05(x-20) | | 3(12-2y)+2y=8 | | 2x^2-37x+66=0 | | -8-12y+5=15 | | 4q-q-(2q-3)= |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics